Aplikasi “W-Triangle” Efektif Meningkatkan Pengetahuan Underwear Rules Pada Anak Usia Sekolah - Sari, Maya; Fauziah, Munaya; Sutini, Titin; Anita, Apriliawati; Purnawati, Tri (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT School age children are children aged 7 - 12 years who are at a stage of development both cognitively, physically, morally and socio-emotionally. This stage begins with the child's entry into the school environment and the child's relationships with other people. According to KPAI data, the highest cases of sexual violence in 2021 were recorded including 536 cases of sexual abuse (62%), 285 cases of rape/coitus, 29 cases of same-sex sexual abuse (3%), 9 cases of same-sex sexual intercourse (1%). ). Providing educational education is facilitated with the help of media that makes understanding easier, including text (booklets), images (posters), sound (radio), audio visuals (video), other media can be objects such as mock ups. One of them uses device technology in the form of an application. The aim of this research is to determine the difference in the influence of education using digital booklet media and the "w-triangle" application on knowledge of underwear rules in school-aged children at SDN Angke 05 Pagi, West Jakarta. This research design uses a two-group pretest-posttest design without control. The sample for this research was taken using proportionate stratified random sampling with a total of 70 children divided into 35 children in the digital booklet education group and the "w-triangle" application. The research results showed that there was a difference in the effect of intervention using digital booklet media and the "w-triangle" application on knowledge of underwear rules with p value = 0.001 (p>0.005). There is a confounding factor that provides the "w-triangle" application on changes in children's knowledge, namely the environment, with p value = 0.012 (p<0.005). Based on the research results, it is suggested that application media can be recommended as an educational medium in pediatric nursing services to prevent sexual violence in school-aged children. Keywords: School Age Children, "W-Triangle" Application, Digital Booklet, Knowledge Of Underwear Rules.  ABSTRAK Anak usia sekolah adalah anak dengan rentang usia 7 -12 tahun berada pada tahap perkembangan baik secara kongnitif, fisik, moral, maupun sosio-emosional. Pada tahap ini dimulai dengan masuknya anak ke lingkungan sekolah dan hubungan anak dengan orang lain. Menurut data KPAI menjelaskan kasus tertinggi kekerasan seksual di tahun 2021 tercatat diantaranya pencabulan sebanyak 536 kasus (62%), pemerkosaan/persetubuhan 285 kasus (33%), pencabulan sesama jenis 29 kasus (3%), persetubuhan sesama jenis 9 kasus (1%). Pemberian edukasi pendidikan difasilitasi dengan bantuan media yang mempermudah pemahaman diantaranya seperti teks (booklet), gambar (poster), suara (radio), audio visual (video), media lainnya dapat berupa objek seperti model tiruan (mock up). Salah satu di antaranya menggunakan teknologi gawai yang berupa aplikasi. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan pengaruh edukasi menggunakan media booklet digital dan aplikasi“w-triangle” terhadap pengetahuan underwear rules pada anak usia sekolah di SDN Angke 05 Pagi Jakarta Barat. Desain penelitian ini menggunakan two-group pretest-posttest design without control. Sampel penelitian ini di ambil dengan cara proportionate stratified random sampling dengan jumlah 70 yang dibagi menjadi 35 anak pada kelompok edukasi booklet digital dan aplikasi “w-triangle”. Hasil penelitian didapatkan ada perbedaan pengaruh intervensi menggunakan media booklet digital dan aplikasi “w-triangle” terhadap pengetahuan underwear rules dengan p value = 0.001 (p>0.005). Ada pengaruh faktor confounding pemberian aplikasi “w-triangle” terhadap perubahan pengetahuan anak yaitu lingkungan dengan p value = 0.012 (p<0.005). Berdasarkan hasil penelitian disarankan media aplikasi dapat direkomendasikan sebagai salah satu media edukasi dalam pelayanan keperawatan anak guna mencegah kekerasan seksual pada anak usia sekolah. Kata Kunci: Anak Usia Sekolah, Aplikasi “W-Triangle“, Booklet Digital, Pengetahuan Underwear Rules.